PELESTARIAN BUDAYA BALI DALAM ARSITEKTUR TAPAK DAN RESTORAN ARUNA RESORT TEJAPRANA TEGALALANG UBUD – BALI - Suryono, Alwin (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2021)
Abstract: Revealing the conservation of Balinese culture forms in the architecture of Site and Aruna Restaurant of Tejaprana resort uses architectural phenomenological approach. The Balinese Culture’s physical-social system is expressed through sensory presence, conceptual systems through goal awareness, and the philosophy through essence awareness. The setting extends from the North-South direction, the Aruna restaurant surrounded by garden in the middle of the site and a temple in the North, preserving the principles of the Balinese Traditional Village setting. The essence of the site order is harmony with the local natural philosophy. Social activities surrounded by gardens in the middle of the site and temple in North form a harmonious-balanced human-nature-God relationship philosophy. The openness of Aruna restaurant is similar to Wantilan's architecture, but with different shape. The pool at the center of the floor and the eight columns around it symbolizes the